ANALISIS AGRIBISNIS SAPI POTONG DI KABUPATEN SIAK PROVINSI RIAU: AGRIBISNIS SAPI POTONG - Nur Khadijah; Syaiful Hadi; Evy Maharani (UNIVERSITAS LANCANG KUNING, 2019)
ABSTRACT. The study aimed to analyze the influence of each subsystem on the income of farmers and between each sub-system is itself on beef cattle farms in Siak. The study was conducted in 4 (four) districts in Siak District of Kerinci Kanan, Lubuk Dalam, Dayun and Koto Gasib using simple random sample selection method . Total sample in this study were 100 breeders. Data were analyzed by scoring and path analysis (path analysis). Path analysis results indicate that the up-stream subsystem to the farmer’s income. influence between the subsystem them are asfollows: Subsystems supporting institutions affecting the entire subsystem of agribusiness; marketing Subsystem affect up-stream subsystem, on-farm subsystem and down-stream Subsystem agribusiness. up-stream subsystem to the on-farm agribusiness, on-farm Subsystem to down-stream agribusiness. The conclusion of research indicated that the implementation of beef cattle subsystem agribusiness had adequate index and give positive effect to the farmer’s income. Keywords: agribusines, up-stream, on-farm, down-stream, marketing, supporting institutions